Analysis of patients with acute pancreatitis in chronic renal failure under haemodialysis - Saritas, Bunyamin; Muslu, Mustafa; Hari, Mustafa; Cetin, Duran Deha; Demir, Fatime; Olmez, Sehmus (Journal of the Pakistan Medical Association, 2026)
Objectives: To evaluate acute pancreatitis in patients with end-stage renal disease on haemodialysis, and to compare it with patients without end-stage renal disease. Method: The retrospective, cross-sectional study was conducted at Adana City Training and Research Hospital, Turkiye, and comprised data from September 2017 to December 2023 of patients presenting with acute pancreatitis with or without end-stage renal disease. Those with end-stage renal disease who were on haemodialysis were placed in group A, while patients without chronic kidney disease represented control group B. Demographic and laboratory data, the severity of pancreatitis, the aetiology of acute pancreatitis, accompanying diseases, the duration of hospitalisation and the prognosis of the patients in both groups were evaluated and compared. Data was analysed using SPSS 25. Results: Of the 178 patients, 54(30.33%) were in group A with mean age 56.0±14.5 years (range: 20-85 years) among whom 26(48.1%) were males. There were 124(69.66%) patients in group B with mean age 52.5±16.2 years (19-88 years), and there were 59(47.6%) males. Acute pancreatitis was more severe, and the number of idiopathic cases was higher in group A compared o group B (p<0.05). Significant differences were also noted for aetiological causes, comorbidities, intensive care unit admission, length of hospital stays, and mortality between the groups(p<0.05). Conclusion: In patients with end-stage renal disease on haemodialysis, acute pancreatitis was more severe in all respects compared to those without chronic kidney disease. Key Words: Acute pancreatitis, Chronic renal failure, Haemodialysis, Survival.